Synthesis and Analgesic and Anti-inflammatory Activity of 6-Phenyl/(4-methylphenyl)-3(2H)-pyridazinon-2-propionamide Derivatives - Gökçe, Mehtap; Colak, Meral Şirin; Kiipeli, Esra; Şahin, Mustafa Fethi (Arzneimittelforschung, 2009)
For reducing gastrointestinal toxicity associated with non-steroidal anti-inflammatory drugs (NSAIDs) a variety of 6-phenyl/(4-methylphenyl)-3(2H)-pyridazi-non-2-propionamide were synthesized. The structures of these new pyridazinone derivatives were confirmed by their IR, 1H-NMR spectra and elementary analysis. All the new compounds were tested in vivo for their analgesic and anti-inflammatory activities. The analgesic activity of the test compounds was determined by phenylbenzoquinone-induced writhing assay and the anti-inflammatory activity was evaluated by the carrageenan-induced rat paw edema model. 6-Phenyl-3(2H)-pyridazinon-2-yl-[4-(4-fluorophe-nyljpiperazinyl] propanamide IV a-3 was the most active one among the synthesized compounds. Also this compound exhibited most potent anti-inflammatory activity. Acetylsalicylic acid and Indometacin were used as reference drugs. Adverse effects of the compounds were examined on gastric mucosa. None of the compounds showed gastric ulcerogenic effect compared with the reference NSAIDs.
Keywords: Arylpiperazines; 3(2H)-Pyridazinone amides, analgesic activity, anti-inflammatory activity